Quantitative and qualitative assessment of contrast-enhanced magnetic resonance imaging of the parotid gland in Sjoegren's syndrome - Stiskal, Michael (Radiology and oncology (Ljubljana), 1999)
Background. The aim of this study was to evaluate the potential of unenhanced and contrast-enhanced MR imaging for providing diagnostic information of the parotid gland in patients with Sjoegren's syndrome. Subjects and methods. In 27 patients with Sjoegren's syndrome, unenhanced and GdDTPA-enhanced spinecho MR imaging was performed. The morphologic MR findings were compared to the signal intensity (SI) measurements of unenhanced T1-weighted, T2-weighted and contrast-enhanced T1-weighted MR imaging. Quantitative and qualitative data were compared with those of normal subjects (n=12). Results. T1 and T2 values on the unenhanced MR images of the patients with Sjoegren's syndrome were significantly lower than those of normal subjects (T1: 62+/-4 %, T2: 71+/-2 % of baseline). Quantitative analysis of contrast-enhanced MR imaging showed a significant SI increase in all patients with Sjoegren's syndrome. Even in 4 patients with no morphologic findings on MR imaging the increase of Sjoegren'ssyndrome MR imaging was significantly higher than in normal subjects(34+/-3% versus17+/-3%; p<0.5. The extend of morphologic changes correlated with quantitative data. The sensitivity and specificity for MR imaging was 85% and 100%, respectively. Conclusions. The use of paramagnetic contrast media provides additional diagnostic information, particulary in the patients without apparent changes in morphology as indicated by a significantly greater tissue enhancement compared to normal subjects. The extent of morphologic alterations corellates with the quantitative data of Gd-DTPA-enhanced MR imaging but not with those of unenhanced MR imaging.
Keywords: Contrast media; Diagnosis; Magnetic resonance imaging; Parotid diseases; Sjogren's syndrome